The Relationship between Duration of Anti-Tuberculosis Treatment and Blood Urea Levels in Patients with Pulmonary Tuberculosis at Bakunase Community Helath Center - Lidia Wulan Stevania Lapudo'oh; Ni Made Susilawati; Byantarsih Widyaningrum; Michael Vallery Loueis Tumbol (Poltekkes Kemenkes Kupang, 2026)
Tuberculosis (TB), caused by Mycobacterium tuberculosis, is a prevalent pathogen requiring prolonged treatment, typically lasting six months. The kidneys, as the primary excretory organs, must intensively filter pharmaceutical compounds throughout this period. This extended regimen can strain renal function and potentially lead to kidney damage, particularly with rifampicin and streptomycin, which have the highest risk of nephrotoxic effects compared to other anti-tuberculosis drugs. This study aimed to determine the relationship between treatment duration and blood urea levels among pulmonary TB patients at the Bakunase Community Health Center using a quantitative observational approach with a cross-sectional design. Researchers collected data with questionnaires and measured urea levels using the BT15i device. The statistical analysis of 30 samples using the Spearman rank correlation test yielded a correlation coefficient of 0,302 (30,2%) and a significance value of 0,105 (p > 0,05). These results indicate no significant correlation between the duration of anti-tuberculosis therapy and blood urea levels. Consequently, the findings suggest that prolonged TB treatment does not lead to a direct increase in urea levels among patients in this clinical setting, indicating that renal filtration remains relatively stable during the standard course of therapy.